Produção de lipídios em Chlorolobion braunii: estímulo induzido por cobre em culturas de 200 L - Pasqualinotto, Guilherme (2025)
Microalgae cultivation has gained prominence in recent years. As a result, several studies and techniques have been developed to increase the viability and yield of compounds produced by microalgae. Strategies such as nutrient, light, and temperature manipulation can increase microalgae productivity. Among these, mixotrophy, which combines organic and inorganic carbon sources, can promote significant biomass gains by combining the advantages of autotrophic and heterotrophic cultivation. Copper, as an essential micronutrient and enzymatic cofactor, exerts a crucial influence on microalgae physiology, impacting metabolism depending on its concentration. The objective of this study was to adapt the strategy described in patent INPI BR 102021019778-1 A2 to 200 L cultures, resulting in increased lipid yield in Chlorolobion braunii. For this purpose, copper at a concentration of 10-8 mol L-1 of free Cu+2 was tested as a manipulating agent, and to increase biomass, mixotrophy was used in the final phase of cultivation. Copper was added to the cultures from the 3rd day onward, while mixotrophy was induced from the 6th day of cultivation using 0.2 g L-1 of sodium acetate (NaO2CCH3). Cultivations were carried out in BG11 medium, in fed-batch mode under semi-controlled conditions in an agricultural greenhouse and lasted 8 days, with natural light and photoperiod. The results showed variation in environmental conditions, with temperature fluctuations of 25,5 – 34,6 °C. Mixotrophy resulted in a threefold increase in biomass production on day 8 of the experiment compared to day 3. As expected, the presence of copper did not affect either the growth rate or the biomass obtained, limiting itself to stimulating lipid production by 23% compared to the control treatment. The copper treatment resulted in a reduction of up to 20% in protein accumulation on day 8 of the experimental period, while total carbohydrates remained constant between the treatments and the control, thus not being influenced by copper. This study emphasizes the biotechnological potential of the microalgae C. braunii and reinforces the importance of optimizing culture conditions to maximize biomolecule production.